2021
DOI: 10.1093/eurheartj/ehab095
|View full text |Cite
|
Sign up to set email alerts
|

The heart of the ageing endurance athlete: the role of chronic coronary stress

Abstract: Moderate physical exercise is associated with an irrefutable reduction in cardiac morbidity and mortality. The current guidelines recommend at least 150 min of moderate exercise or 75 min of vigorous exercise per week. Endurance athletes perform exercise at a level that is 10- to 20-fold greater than these recommendations. These athletes reveal several structural and functional cardiac adaptations including increased cardiac size, enhanced ventricular filling, and augmentation of stroke volume even at the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Overall, the long-term effects of endurance exercise on the heart are widely unknown. Endurance exercise is associated with a transient increase of biomarkers of cardiac damage and there is growing evidence that lifelong male athletes aged above 40 years show a higher prevalence of a higher coronary plaque burden, and a different MF pattern compatible with subclinical infarction compared with relatively sedentary healthy controls (32). As no adequate data were available for females, no sex-specific conclusions could be safely drawn from our analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, the long-term effects of endurance exercise on the heart are widely unknown. Endurance exercise is associated with a transient increase of biomarkers of cardiac damage and there is growing evidence that lifelong male athletes aged above 40 years show a higher prevalence of a higher coronary plaque burden, and a different MF pattern compatible with subclinical infarction compared with relatively sedentary healthy controls (32). As no adequate data were available for females, no sex-specific conclusions could be safely drawn from our analysis.…”
Section: Discussionmentioning
confidence: 96%
“…From a clinical point of view, high prevalence of masked hypertension in middle-age ambitious male athletes may explain some of the complications characteristic of this population such as high coronary calcium score, high atherosclerotic plaque burden, myocardial fibrosis or higher risk of atrial fibrillation in comparison to general population [ 8 , 21 ]. A previous meta-analysis demonstrated that patients with masked hypertension, despite only mildly elevated BP values, have significantly increased rates of cardiovascular events and all-cause mortality than normotensives [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finding of amplitude criteria for LVH in electrocardiogram (ECG) or mild, concentric LVH on transthoracic echocardiogram may often be rationalized as part of physiological adaptation and not lead to additional tests and a more detailed BP assessment [ 2 , 7 ]. Leaving master athletes with undiagnosed hypertension, even mild, puts them at risk of future complications such as aortic dilation, left atrial enlargement with the risk of atrial fibrillation, LVH with fibrosis and the risk of ventricular arrhythmias, diastolic dysfunction of the heart or acceleration of atherosclerosis [ 4 , 8 ]. All these complications may reduce the benefits of regular PA and lead to myocardial infarction, strokes, heart failure, disability and higher mortality in comparison to athletes without or with treated hypertension [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through serial PA measurements, we identified three distinct trajectory groups that better summarise subjects’ behaviour over a 25-year period of time in early adulthood than a single measure of PA at year 0 (beginning of the cohort) or year 15 (date of CAC first measurement). In addition, unlike previous studies focusing on elite and amateur athletes,37–39 we recruited a general population of young adults free of CVD events at baseline. Among the participants in this general population cohort, our model did identify a group of adults with a trajectory which combines a PA three times the guideline recommendations or more, in average, and a particular pattern of change in their PA from early adulthood for a 25-year observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Plausible explanations could account for this paradox. Prolonged high levels of PA-induced increase in cardiac output may increase mechanical stress on the epicardial coronary arteries, leading to vessel wall injury and accelerated atherosclerosis 39. Furthermore, high levels of PA increase blood pressure, parathyroid hormone levels, and several pro-inflammatory factors, all of which are involved in CAC progression 2.…”
Section: Discussionmentioning
confidence: 99%